Finanças Comportamentais e Vieses nas Decisões de Investimento - Andriotta, Carina Thaís (2023)
This study seeks to understand the cognitive biases and heuristics that influence decision-making and strategy adoption in Brazilians' personal investments. To achieve the general objective of the present study, which is to relate the investment behavior of Brazilians with the biases and heuristics listed in behavioral finance, a literature review was carried out on the topic of behavioral finance, focusing on identifying the main heuristics and biases. In addition, characteristics of Brazilians were identified through the study of Investor X-Ray surveys by the Brazilian Association of Financial and Capital Market Entities (ANBIMA). In summary, the analysis of investor X-ray data demonstrated that there is a large discrepancy in reality between classes A, B and C and classes D and E with regard to financial knowledge and behavior. Most of the Brazilians investigated were unable to make some type of investment or save money, due to unsatisfactory financial conditions, in addition to a high percentage not knowing any type of investment on the market.